1999
DOI: 10.1136/bjsm.33.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Injury rates in Shotokan karate.

Abstract: Objective-To document the injury rate in three British Shotokan karate championships in consecutive years. In these tournaments strict rules governed contact, with only "light" or "touch" contact allowed. Protective padding for the head, hands, or feet was prohibited. Methods-Prospective recording of injuries resulting from 1770 bouts in three national competitions of 1996, 1997, and 1998. Details of ages and years of karate experience were also obtained. Results-160 injuries were sustained in 1770 bouts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
36
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 10 publications
12
36
2
1
Order By: Relevance
“…In our study, four wrestlers sustained head trauma that required treatment at the emergency outpatient clinic in 817 matches, giving an injury rate per match of 0.5%. The frequency of head trauma per match is 5.1% (91 cases/1,770 matches) in Shotokan karate (U.K.), 6) 22.5% (96/427) in professional boxing (Australia), 24) and 5.7% (197/3,481) in professional kick boxing (Australia). 25) Compared with these values, the frequency of head trauma per match in our female wrestlers was low, but only 13 regular wrestlers had 817 matches in 14 months, so the number of matches fought per wrestler was clearly higher than in other martial arts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, four wrestlers sustained head trauma that required treatment at the emergency outpatient clinic in 817 matches, giving an injury rate per match of 0.5%. The frequency of head trauma per match is 5.1% (91 cases/1,770 matches) in Shotokan karate (U.K.), 6) 22.5% (96/427) in professional boxing (Australia), 24) and 5.7% (197/3,481) in professional kick boxing (Australia). 25) Compared with these values, the frequency of head trauma per match in our female wrestlers was low, but only 13 regular wrestlers had 817 matches in 14 months, so the number of matches fought per wrestler was clearly higher than in other martial arts.…”
Section: Discussionmentioning
confidence: 99%
“…Head trauma suffered during sports activities is well known, 1,2,6,7,13,14,16,21,[23][24][25] and incidents associated with snowboarding have increased recently with the rise in the popularity of the sport. 19) Professional wrestling in Japan has lead to the deaths of two female and one male wrestlers due to head trauma since 1997, 20) but these incidents have not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another study showed a threefold increased risk of injury and a higher risk of multiple injuries in taekwondo compared with karate. 13 Of 5 martial arts disciplines (Shotokan karate, Aikido, taekwondo, kung fu, and tai chi), taekwondo had the highest number of injuries requiring time off from training (59%). 14 Taekwondo has a high relative incidence of lower extremity injury compared with upper extremity injury because 80% of its competitive moves involve powerful, fast kicks.…”
Section: Injury Riskmentioning
confidence: 99%
“…In other words, in Karate, one uses different technics of kicks (leg) and punches (hand) and defends without the using of any firearms. It is practiced in two fields of KATA (practice of a collection of techniques against no direct fighters), and KUMITE (fighting against real opponents) (Critchley & Meredith, 1999;Emmermacher et al, 2007;. Techniques like URA MAWASHI GERI, UKO GERI KEAGE, GER KEAGE, YOKO GERI KEKOMI, MAE GERI and MAWASHI GERI and etc., are performed by leg.…”
Section: Introductionmentioning
confidence: 99%